2020
DOI: 10.1177/0731948720944164
|View full text |Cite
|
Sign up to set email alerts
|

The Social and Academic Effects of Cooperative LEARN Strategy Instruction in Inclusive Elementary Classes

Abstract: This study reports the effects of instruction of elementary students in a complex package of social and academic skills designed for use in cooperative groups while studying important information in inclusive general education classes. Twenty-five teachers and 519 fourth and fifth graders, including 45 students with learning disabilities (LD), participated. A pretest/posttest control-group design with random assignment was used to determine the effects of the instructional program. Data were analyzed for stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…With some major change occurring in CTLArelated sub-scales: positive interdependence (gain=2.87), promotive face-to-face interaction (gain=2.25), individual accountability (gain=2.05), and group processing (gain=2.05). This observation as recorded in this study is in line with the results of recent studies (D'Eon & Zhao, 2022;Fernández-González & Franco-Mariscal, 2021;Jurkowski & Hänze, 2015;Nam & Zellner, 2011;Vernon et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…With some major change occurring in CTLArelated sub-scales: positive interdependence (gain=2.87), promotive face-to-face interaction (gain=2.25), individual accountability (gain=2.05), and group processing (gain=2.05). This observation as recorded in this study is in line with the results of recent studies (D'Eon & Zhao, 2022;Fernández-González & Franco-Mariscal, 2021;Jurkowski & Hänze, 2015;Nam & Zellner, 2011;Vernon et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
“…Specifics is made on the social constructivism, which according to Prawatt and Floden (1994) maintain that the social nature of knowledge, the belief that knowledge is the result of social interaction and language usage, and thus is a shared, rather than an individual experience. As result, a meaningful learning occurs when individuals engage in social activities and consequently unite into a "dynamic whole"; in this way innovations from individual learners could be modified to reflect innovations of learners working together in groups (Kyndt et al, 2013;Roseth et al, 2008;Vernon et al, 2022). The theory therefore positions the facilitator to drive the individual learners' intrinsic motivation towards the completion of a task (Hamadi et al, 2022).…”
Section: Towards the Conceptualization Of The Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a logical notion that follows these findings is that social skills instruction might be one intervention of choice, not only to address behavior problems but also to improve interpersonal skills (Durlak et al, 2011;Gresham, 1998;Gresham et al, 2001;Mathur & Rutherford, 1994;Mathur et al,1998;Osher et al, 2008;, Vernon et al, 1996, 2020. Loeber and Farrington (1998), for example, suggested that the most effective treatments for youth with adjustment problems incorporated interpersonal skill training.…”
Section: Social Skills Instruction As An Optionmentioning
confidence: 99%